2018
DOI: 10.1002/eqe.3054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irregular structural configuration on floor acceleration demand in hill‐side buildings

Abstract: Summary A suite of reinforced‐concrete frame buildings located on hill sides, with 2 different structural configurations, viz step‐back and split‐foundation, are analyzed to study their floor response. Both step‐back and split‐foundation structural configurations lead to torsional effects in the direction across the slope due to the presence of shorter columns on the uphill side. Peak floor acceleration and floor response spectra are obtained at each storey's center of rigidity and at both its stiff and flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The torsion angle of the upper ground floor is always the maximum. The similar conclusion was also drawn from the previous research (Surana et al, 2016, 2018a, 2018b). The normalized floor eccentricity of the upper ground floor is the largest, which indicates that there is significant torsional effect in the upper ground floor.…”
Section: Parametric Analysissupporting
confidence: 91%
“…The torsion angle of the upper ground floor is always the maximum. The similar conclusion was also drawn from the previous research (Surana et al, 2016, 2018a, 2018b). The normalized floor eccentricity of the upper ground floor is the largest, which indicates that there is significant torsional effect in the upper ground floor.…”
Section: Parametric Analysissupporting
confidence: 91%
“…In the present study, CR is obtained considering the definition of the single floor eccentricity. The additional details about estimation of CR in the investigated step-back building is available elsewhere [21]. Based on the obtained estimates of the eccentricity between CM and CR, it is observed that in the investigated irregular step-back building, the maximum torsional effects exist at the base floor (Fig.…”
Section: Dynamic Characteristics and Torsion In The Investigated Buildingsmentioning
confidence: 94%
“…As highlighted in the past research [2][3][4][5][6][7][8], the floor response is significantly affected by the dynamic characteristics of the building, therefore, the dynamic characteristics of the investigated buildings are summarized in Table 1. Past investigations [21] on irregular step-back buildings suggest that in such buildings, the period corresponding to the fundamental mode of vibration is usually controlled by the number of storeys measured on the uphill side (Fig. 1(d)), irrespective of the direction under consideration.…”
Section: Dynamic Characteristics and Torsion In The Investigated Buildingsmentioning
confidence: 97%
“…They observed that with the increase in building inelasticity, the participation of higher modes of vibration increases, and PFA/PGA are reduced in most cases, though some exceptions also exist. Surana et al 25 . showed PFA/PGA increases at the flexible edge (FE) compared to the CR in the elastic step‐back and split‐foundation buildings.…”
Section: Introductionmentioning
confidence: 99%